EFFECT OF COMMERCIAL RATION REPLACEMENT WITH FERMENTED GREEN BEAN SPROUT WASTE FLOUR ON THE PHYSICAL CARCASS COMPOSITION OF MALE BALI DUCK - I P. G., Wiyardana; Siti, N. W.; Sukmawati, N. M. S. (Jurnal Peternakan Tropika; Vol 8 No 2 (2020): Vol. 8 No. 2 Tahun 2020; Mei - Agustus, 2020)
Research that aims to determine the effect of commercial ration replacement with fermented green bean sprout waste flour on the physical carcass composition of male bali duck at the age of 8 weeks has been carried out at the Farm Faculty of Animal Husbandry, Udayana University on Jl. Raya Sesetan Markisa Gang No. 5, Denpasar, Bali. The study used a completely randomized design (CRD) consisting of 3 settings and 5 replications. Each repetition used 3 male Bali ducks, so that the total ducks used were completely 45 with the average weight range of 43.8 g ± 0.96 g. The treatments are: P0 (100% commercial ration), P1 (12.5% ??replacement of commercial ration with fermented green bean sprout flour) and P2 (replacement of 25% commercial ration with fermented green bean sprout flour). The variables observed were slaughter weight, carcass weight, carcass percentage, physical carcass composition (percentage of meat, bone and subcutaneous fat including skin). The results showed that the replacement of 12.5% ??and 25% of commercial rations with fermented green bean sprouts flour had no significant effect (P> 0.05) on slaughter weight, carcass weight, carcass percentage, physical carcass composition. It can be coneluded that the replacement of commercial rations with fermented green bean sprout waste flour until level of 25% has no effect on physical carcass composition of male bali duck aged of 8 weeks.   Keywords: male Bali duck, fermented green bean sprout flour, physical carcass composition,                  commercial ration